Where is the Support? Learning Support for Multimodal Digital Writing Assignments by Writing Centres in Canadian Higher Education - Stephanie Bell; Brian Hotson (Canadian Journal for the Scholarship of Teaching and Learning, 2021)
Writing centres play a vital role in supporting all forms of student academic writing in higher education (HE) institutions, including digital writing projects (DWPs)—multiliterate and multimodal, often video-and-audio-based projects, produced using digital technologies. The importance of writing support for multimodal composing is evident in emerging research on both the multi-skilled practices of writer-designers and the conceptual shifts involved in their adoption. Currently, no research exists regarding the Canadian context of writing centre support for DWPs. To address this, we conducted two surveys: one of 22 Canadian writing centres asking about DWPs prevalence, technology and skills readiness, and DWP awareness; and one of faculty at a large Canadian university, asking about DWPs prevalence and frequency and types of DWP assignments. We find a significant disconnect between the number of DWPs being assigned by faculty and the number being supported in writing centres. We also find a significant lack of writing centre preparedness for supporting DWPs. This paper calls, with some urgency, for writing centres to invest in the reality of student writing in Canadian HE, to begin developing instructional materials, equipment, and skilled staff to support DWPs.